Effect of Isoflavon Genestein Daidzein from Pueraria Lobata Extract on Vascular Endothelial Growth Factor Expression in The Aorta of Hypoestrogenic Rat - Akhmad Suaidi; Achmad Hidayat; Wening Hapsari (Asian Journal of Health Research, 2022)
Introduction: Currently, there is no research about the effect of isoflavone-based phytoestrogens on the expression of VEGF in arteries which play a role in preventing vascular diseases in menopause women (hypoestrogenic state). We want to know the effect of Isoflavone Genistein Daidzein in Pueraria lobata extract on VEGF expression in the arterial endothelium of hypoestrogenic rats. Methods: This is an analytical, experimental study with a post-test-only control group design. Subjects were Wistar strain rats (Rattus novergicus) randomized into five groups of different treatments by simple random sampling. The aorta was then examined for VEGF expression. Statistical analysis used were ANOVA, followed by multiple comparison tests by the Tukey Honestly Significant Difference and regression test with SPSS series 11.0. The analysis is significant if p < 0.05. Results: Isoflavone Genistein Daidzein (IGD) in Pueraria lobata extract will increase the expression of hypoestrogenic rat endothelial VEGF. IGD dose of 15 mg/kg BW/day resulted in VEGF expression with an average of 6.67 ± 2.94,30 mg/kg BW/day with an average of 9.83 ± 2.71, and 60 mg/kg BW/day with an average of 9.83 ± 2.71 (p<0.05). Conclusion: VEGF in arteries of hypoestrogenic rats without IGD supplementation was not significantly different from VEGF in the average rats. There was a significant positive effect on VEGF expression in hypoestrogenic rat arteries due to the administration of IGD in Pueraria lobata extract.